SiO2-Modified Separators: Stability in LiPF6-Containing Electrolyte Solutions and Effect on Cycling Performance of Li Batteries. Issue 8 (21st May 2019) - Markevich, Elena; Salitra, Gregory; Afri, M.; Kulisch, Joern; Hartmann, Pascal; Aurbach, Doron
Abstract : Significant improvement in the performance of cells comprising Li metal anodes and LiNi0.6 Co0.2 Mn0.2 O2 (NCM 622) cathodes with practical loading of the electrodes material (3.3 mAh cm −2 ) and low amount of the electrolyte solution (22 μl cm −2 ) was achieved with the use of SiO2 filled polyethylene separators. The effects of cycling and storage on the stability of the SiO2 filled separators in fluoroethylene carbonate (FEC) and LiPF6 -containing electrolyte solutions was studied with the use of Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy and X-ray diffraction. We analyzed the composition of the separators and the gas phase after storage and cycling of these cells. Although SiO2 reacts with LiPF6 when the separator is in contact with the electrolyte solution, we showed that it is fully stable during cycling in the Li-NCM622 cells. The formation of lithium hexafluorosilicate (Li2 SiF6 ) on SiO2 filled separators and tetrafluorosilane (SiF4 ) in the gas phase around them was detected when these separators were stored in the electrolyte solutions without cycling. The effect of the electrodes and the operation condition on the stability of SiO2 containing separators is discussed.